Grenzen auflösen - Grenzen ziehen Grenzbearbeitungen zwischen Erziehungswissenschaft, Politik und Gesellschaft - Frank, Magnus; Geier, Thomas; Hornberg, Sabine; Machold, Claudia; Otterspeer, Lukas; Singer-Brodowski, Mandy; Stošić, Patricia (Verlag Barbara Budrich, 2023)
The boundaries between science, politics and society are fluid and are constantly being reestablished. This volume is dedicated to this topic, bringing together contributions from the annual conference of the Section for Intercultural and International Comparative Education 2021 (SIIVE) in the German Society for Educational Science (DGfE). It opens up theoretical and empirical perspectives on boundary treatments, takes stock of boundary treatments, focuses on methodological-methodological challenges and works on borders.